So the problem is asking you to combine equations, in this case the Y factor will cancel out so you will be left with the X factor and the total after you add both of the totals together,
6x-4y=16
5x+4y=6
6x-5x=x
16+6=22
x=22
Answer:
2√13
Step-by-step explanation:
The distance formula is useful for this. One end of the vector is (0, 0), so the measure of its length is ...
d = √((x2 -x1)² +(y2 -y1)²) = √((6 -0)² +(-4-0)²)
= √(36 +16) = √52 = √(4·13)
d = 2√13 = |(6, -4)|
Answer:
Dependent
Step-by-step explanation:
There is a 1/3 chance that 1 of the first 3 people will pick Jerry's favorite kind of doughnut
So I think it is dependent
Answer:
AB = 8.4
Step-by-step explanation:
the Pythagorean therm
find the square root of 6(squared + 6(squared) = 8.4
Radius = 6 so the other side is the same